1996
DOI: 10.1021/jp9515693
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory Study of Molecular Structures and Vibrational Spectra of 3,4- and 2,3-Pyridyne

Abstract: Density functional theory and ab initio MP2 6-31G* calculations were carried out to investigate the structures and vibrational spectra of 3,4- and 2,3-pyridyne. It is found that the structure of 3,4-pyridyne is consistent with a formal CC triple bond moiety, but the structure of 2,3-pyridyne is more properly described as having a unit. On the basis of the calculated results, detailed assignments of the observed IR bands of 3,4-pyridyne are proposed. The calculations predict the most prominent IR feature of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…The calculation of vibrational frequencies using DFT provides a promising cost-effective approach for calculating vibrational spectra of large molecules. In the recent theoretical studies, the harmonic vibrational frequencies for a larger number of small and well-studied organic ligands were computed with HF and DFT methods [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The calculation of vibrational frequencies using DFT provides a promising cost-effective approach for calculating vibrational spectra of large molecules. In the recent theoretical studies, the harmonic vibrational frequencies for a larger number of small and well-studied organic ligands were computed with HF and DFT methods [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that vibrational frequencies calculated by DFT methods are more reliable than those obtained at MP2 level. 7,8 For VCD spectra calculations, the implementation of direct analytical derivative methods for calculating HFFs, APTs, and AATs 9 is of most importance. Incorporation of gauge invariant atomic orbitals (GIAO) into the calculation of AATs makes it possible to predict the VCD spectra using the DFT method.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that molecular structures and vibrational frequencies calculated by DFT methods are more reliable than MP2 methods [11][12][13]. There is sufficient evidence that DFT provides an accurate description of the electronic and structural properties of solids, interfaces, and small molecules.…”
Section: Introductionmentioning
confidence: 99%